Progress and Poverty in Current Literature on Valuation - Bonbright, James C. (Quarterly Journal of Economics, 1926)
The publications reviewed: Bauer, Lyndon, Maltbie, Nash, Raymond. — I. Retrospective and prospective regulation as affecting the basis of valuation, 297. — II. Valuation as a means of controlling profits and as a means of controlling charges, 302. — III. The market value fallacy in the determination of "fair value, " 307. — IV. Consistency in the development of a valuation theory, 314. — V. Conclusions, 325.